PERUMAHAN DAN PERMUKIMAN BERKELANJUTAN: SOLUSI INOVATIF UNTUK TANTANGAN PERKOTAAN MASA KINI - Ayesha Amiranti Putri Masagung; Prasetyo, Prasetyo (Bajang Institute, 2025)
he rapid pace of urbanization in the modern era presents significant challenges in managing housing and settlements, particularly concerning environmental, economic, and social sustainability. One of the main challenges is preventing housing and settlements from becoming centers of slum growth, which can deteriorate the quality of urban life. This article explores the concept of sustainable housing and settlements as an innovative solution to address these issues. By integrating principles of energy efficiency, responsible natural resource management, and inclusive design that fosters social cohesion, sustainable housing meets the demand for adequate living spaces without compromising future sustainability. This study also highlights strategies to prevent slum development through good governance, participatory planning, and the integration of basic infrastructure such as sanitation, clean water, and green open spaces. Moreover, the application of eco-friendly technologies, the utilization of renewable energy, and community-based designs are key to creating healthy and orderly environments. The findings reveal that sustainable housing and settlements not only offer practical solutions to urbanization challenges but also contribute to preventing the emergence of slums while building resilient, inclusive, and environmentally friendly cities. These insights are expected to serve as a reference for the planning and development of future cities